SMALL TALK IN ROGER MICHELL’S MOVIE “NOTTING HILL” IN ENGLISH LITERATURE IN 2019 AT UNIVERSITAS NEGERI MAKASSAR - Suwina, Nuralifdah; Iskandar, Iskandar (Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This article seeks and examines the types and impact of small talk in movies. The subject is Notting Hill, Roger Michell's. This article uses qualitative research techniques. Data is collected after watching the movie. The types of small talk are grouped using the theory of John Spacey (2018) and the impact that is in the film is analyzed by the ideas of Twenge, Jean M. & Campbell, W. (2009). The findings show that: (1) First, there are eight types of small talk in the movie